Climatic Change and Variability in Dehrudun City, Uttarakhand - Rawat, M.S.S.; Singh, M.P. (National Geographical Journal of India, 2022)
Climate, like any other physical phenomenon, is not static but rather a fairly dynamic. There are secular changes in the weather and climate at global, regional and local level due to natural factors. Human body canfunction properly only in favourable climatic condition in term of oxygen, heat, light, humidity and precipitation, wind, lightning, fog, clouds, atmospheric electricity and space. Since variability is an established fact we must identify management practices and techniques appropriate for changed climatic behaviour. Thus, if all these solutions are implemented correctly in an organised and planned manner the days are not far off when Dehradun will be considered the most beautiful, organised and dream city to live in.